Existentialism and A. Camus’ Fiction - Bartkus, Gvidonas (Problemos, 1969)
Camus solves principal problems in his works like other existentialists do. Although his philosophical outlook is idealistic, his writing should not be ignored. In “The Stranger” humanistic tendencies manifest themselves in that the writer protects the man against the society levelling him down to the common standard. Both in “The Stranger” and in “The Plague” the assertion of man’s joy of existence is felt. Dealing with absurdity in “The Plague” the writer contends that there exist moral values in a common human framework that ennoble him.